Analysis of Magmatic Crystal Destruction by Backscattered Electron Imaging. (September 2022) - Sturm, Robert
Abstract : Abstract: After their crystallization from magmatic melt, minerals such as accessory zircon are often subject to different kinds of chemical impairment. This includes the radiation-induced damage of the crystal lattice due to the incorporation of radioactive elements (U, Th) and the dissolution of the mineral structure due to the permanent action of aggressive fluid phases. Both phenomena can be best studied by using specific crystal sections and electron microscopy visualization techniques (backscattered electron imaging, BSEI). Crystal damage by the emission of α-particles corresponds to a continuous transformation of the regularly structured lattice into an amorphous mass. Mineral dissolution is expressed by the formation of specific corrosion pits, which may be refilled by recrystallized material.